2022
DOI: 10.3389/fnut.2022.838179
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides as Potential Anti-tumor Biomacromolecules —A Review

Abstract: Cancer, as one of the most life-threatening diseases, has attracted the attention of researchers to develop drugs with minimal side effects. The bioactive macromolecules, such as the polysaccharides, are considered the potential candidates against cancer due to their anti-tumor activities and non-toxic characteristics. The present review provides an overview on polysaccharides' extraction, isolation, purification, mechanisms for their anti-tumor activities, structure-activity relationships, absorption and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 127 publications
0
36
0
Order By: Relevance
“…Modern pharmacological studies show that polysaccharides from the traditional Chinese medicine have anti-tumor, immunity enhancing, anti-inflammatory, and anti-oxidation effects as well as helping to regulate the intestinal microenvironment ( 25 29 ). It is shown that polysaccharide can easily be depolymerized during the extraction process, and starch can easily be gelatinized and denaturalized ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern pharmacological studies show that polysaccharides from the traditional Chinese medicine have anti-tumor, immunity enhancing, anti-inflammatory, and anti-oxidation effects as well as helping to regulate the intestinal microenvironment ( 25 29 ). It is shown that polysaccharide can easily be depolymerized during the extraction process, and starch can easily be gelatinized and denaturalized ( 30 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we found that the extraction of polysaccharides in soups prepared by the boiling processes that used an additive (processes 2, 3, 4, and 5) was generally better than when using only pure water (daily process and process 1), regardless of the type of additive used. Modern pharmacological studies show that polysaccharides from the traditional Chinese medicine have anti-tumor, immunity enhancing, anti-inflammatory, and antioxidation effects as well as helping to regulate the intestinal microenvironment (25)(26)(27)(28)(29). It is shown that polysaccharide can easily be depolymerized during the extraction process, and starch can easily be gelatinized and denaturalized (30).…”
Section: Effects Of Different Boiling Processes On Total Polysacchari...mentioning
confidence: 99%
“…Polysaccharides possessing sulfur and uronic acids displayed antioxidant potential and anti-cancer properties by restoring cell redox control ( 100 , 101 ). The most prevalent mechanisms of anti-tumor polysaccharides are cell cycle arrest, anti-angiogenesis, and apoptosis, all of which have direct tumor-killing abilities ( 102 ). Polysaccharide anti-tumor action is determined by the main chain configuration ( 103 ).…”
Section: Prebiotic Properties Of Microbial Polysaccharidesmentioning
confidence: 99%
“…Polysaccharides, very important bioactive macromolecules, have long been used as additives in healthy foods due to their various biological effects and in emulsions to improve texture, water retention, and stabilization ( 10 ). These molecules are proven to have antioxidative, hypolipidemic, and anti-tumor activities ( 11 13 ). The complex structures of polysaccharides, including the variety of monosaccharide components and the various linkage and configuration patterns, give them their diverse functional properties ( 14 ).…”
Section: Introductionmentioning
confidence: 99%